Specific cutting energy optimization of CF/PEEK milling considering size effect. (15th October 2022) - Song, Yang; Cao, Huajun; Qu, Da; Yi, Hao; Huang, Xuefeng; Kang, Xinzhen; Yan, Chunping
Highlights: Workpiece self-action in machining CFRP is revealed considering size effect. Light springs model was presented as a manifestation of workpiece self-action. Cutting mechanisms of CFRP with 0° fiber orientation was first clarified, including bending, stretching and delamination, pressing, bouncing and delamination. Based on surface integrity, SCE was diagnosed to define effective SCE for optimizing cutting parameters. Abstract: As the radius of carbon fibers and cutting edge are in the same order of magnitude, workpiece self-action, which could not be neglected in machining Carbon Fiber Reinforced Polymer (CFRP) considering size effect, has become a new perspective. Specific Cutting Energy (SCE) is a significant indicator for chip formation, cutting forces, tool wear, and machined surface integrity. Based on this, we presented a light springs model to clarify workpiece self-action to establish a specific cutting energy (SCE) prediction model of high speed dry (HSD) milling CFRP. The light springs model, which was also a direct reflection of the size effect, reflected the interaction of carbon fibers, interfaces and the matrix. The carbon fibers distribution in the chip was counted to confirm the light springs deformation at different position as carbon fiber and interface are consisted of the light spring. First of all, based on workpiece self-action and elastic-plastic theory, the cutting mechanisms were clarified to calculate SCE with high prediction accuracy (maximum relative error 7.7%). Furthermore, SCE distribution was obtained based on different cutting mechanisms, including bending, stretching, delamination and pressing bouncing. To improve machined surface integrity, three-dimensional (3D) arithmetic mean height and 3D fractal dimension were used for quantitative characterization of the surface integrity. The paper defined integrated evaluation indexes SCEDS and SCESa to reflect effective SCE to optimize milling parameters based on correlation analysis of SCE distribution and surface quality, founding that HSD milling operation could reduce machining defects. Graphical abstract: Image, graphical abstract